Pengajaran sastra bahasa Jerman bagi pemula - Wahyu Kurniati Asri; Burhanuddin Burhanuddin; Ambo Dalle; Abd. Kasim Achmad (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
German currently is one of the foreign language thathas become part of the education curriculum in Indonesia andhave taught on the level of education high school (HIGHSCHOOL) until at College. German learning objectives inIndonesia is so that students have a basic ability in speakingskills to communicate in simple German including the literaryand cultural study. This is in accordance with the curriculumof language competence in German basically such as thestudents expected to compile oral and write simple texts inaccordance with the linguistic and cultural elements found inthe literature. Teaching language literature Germany werecombined into four language skills among others in the skillsof reading, listening, reading and writing are also included inthe learning of grammar, and vocabulary as well. Theproblems facing German in the field of language teachers isthe average they had never taught their students to Germanliterature. Therefore, the activities of this communityPartnership Program they are given training in the teaching ofGerman literary. In the activities of this communitypartnership program that involved Germany language teachersare included in the bond of language teachers (IGBJI) GermanIndonesia Makassar branch as much as 13 people. Thematerial provided on the Community Partnership Program isteaching language literature Germany. Literary works inquestion are: Liedtext, Gedicht, Visuelles Sprachspiel, BildSprach-Spiel,Kurze Geschichte, etc. The teacher looks veryenthusiastic and motivated to follow this training.